(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
For precise application, it is imperative to provide accurate and stable performance. The feed flow rate of a syringe fluid dispensing system is regulated through a Proportional- Integral-Derivative (PID) and Active Force Control (AFC) control scheme that was actuated using a DC servo motor considering a real-time implementation. The focus of this study is to control the speed of a DC motor by implementing an AFC strategy in rejecting the disturbance in the system. The AFC is implemented by cascading its control loop with the outer PID controller loop to form a two degree-of-freedom (DOF) controller. The performance of the proposed PID with AFC control scheme was investigated considering both the theoretical simulation and experimental works. The simulation was performed in MATLAB/Simulink computing platform while the real-time experimentation was done by utilising the Arduino MEGA 2560 microcontroller with MATLAB/Simulink driver for the data acquisition, interface and control implementation. The results implies the robustness of the AFC-based system in controlling the feed flow rate of the fluid in the dispenser. The best performance is obtained for 100% AFC with the disturbance due to vibration almost completely compensated via the proposed scheme in comparison to the PID counterpart.